2014
DOI: 10.1186/1471-2407-14-539
|View full text |Cite
|
Sign up to set email alerts
|

Promoting E2F1-mediated apoptosis in oestrogen receptor-α-negative breast cancer cells

Abstract: BackgroundBecause oestrogen receptor α (ERα) regulates E2F1 expression to mediate tamoxifen resistance in ERα-positive breast cancer cells, we aimed to define the possible roles of ERα and E2F1 in promoting the resistance of ERα-negative breast cancer cells to 4-hydroxy-tamoxifen (4OHT).MethodsThis study utilised conventional techniques to demonstrate the effects of 4OHT on the expression of ERα and E2F1 and also examined the individual and combined effects of 4OHT with dipyridamole (DIPY) and 3-O-(3,4,5-trime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
0
11
1
Order By: Relevance
“…Other BC cell lines harboring p53 mutations, such as MDA-MB-231 and 4T1, are highly resistant to both apoptosis and the induction of senescence after IR. Although we recently demonstrated that the HMT highly sensitized these cells to E2F1-dependent apoptosis, 12 , 19 in this study, we observed a strong synergy between this treatment and radiotherapy ( Figure 4e ). As shown in Figure 4d , radiation of MDA-MB-231 and 4T1 cells in the presence of HMT significantly increased the proportion of apoptotic cells with respect to HMT-treated cells.…”
Section: Resultscontrasting
confidence: 58%
See 1 more Smart Citation
“…Other BC cell lines harboring p53 mutations, such as MDA-MB-231 and 4T1, are highly resistant to both apoptosis and the induction of senescence after IR. Although we recently demonstrated that the HMT highly sensitized these cells to E2F1-dependent apoptosis, 12 , 19 in this study, we observed a strong synergy between this treatment and radiotherapy ( Figure 4e ). As shown in Figure 4d , radiation of MDA-MB-231 and 4T1 cells in the presence of HMT significantly increased the proportion of apoptotic cells with respect to HMT-treated cells.…”
Section: Resultscontrasting
confidence: 58%
“…Unless otherwise indicated, cells were treated with the HMT (consisting of a combination of 10 μ M TMCG and 5 μ M DIPY) for 72 h. This single concentration dose regimen was chosen based on previous studies carried out in our laboratory, where the effects of single treatments (TMCG or DIPY) on BC cells can also be observed. 12 , 19 For treatments involving HMT combined with IR (IR/HMT), after 3 days of treatment with the HMT, the cells were irradiated at the indicated doses. For ionizing radiation (IR) assays, the cells were irradiated using an Andrex SMART 200E machine (YXLON International, Hamburg, Germany) operating at 200 kV, 4.5 mA with a focus-object distance of 20 cm at room temperature and at a dose rate of 2.5 Gy/min.…”
Section: Methodsmentioning
confidence: 99%
“…E2F1) have been associated with tamoxifen resistance in ERpos breast cancer cells. 130 Until now, intra-and intertumoral heterogeneity of downstream effectors is only sparsely analyzed. Gorges et al 66 revealed intratumoral heterogeneity of PI3K downstream effectors by multiplex transcriptome profiling of single CTCs.…”
Section: Growth Factor Signaling (Pi3k/akt/mtor/ Foxo)mentioning
confidence: 99%
“…Genome-wide analysis of targets of E2F1 using microarrays has also identified a large number of genes that are regulated by E2F1 in diverse cellular processes, such as replication, apoptosis, checkpoint control and DNA repair (9). In tumor biology, aberrant expression of E2F1 has been detected in various cancer cell lines and clinical tissues, including amplification of the E2F1 gene in erythroleukemia cell lines, elevated expression of E2F1 protein in breast cancer cell lines and head and neck carcinoma cell lines, and overexpression of E2F1 in invasive ductal breast cancer and non-small cell lung cancer, where high E2F1 expression associates with advanced disease and poor prognosis (10)(11)(12)(13)(14). Particularly, Ren et al (15) observed that E2F1 expression was elevated in advanced PCa and found that E2F1 knockdown could inhibit prostate tumor growth in vitro and in vivo through sensitizing tumor cells to ICAM-1 mediated anti-immunity by NF-κB modulation, highlighting the potential of E2F1 as a therapeutic target; Davis et al (16) indicated that elevated E2F1 expression, through its ability to repress androgen receptor (AR) transcription, might contribute to the progression of hormoneindependent PCa; Zheng et al (17) found that E2F1 could induce cancer cell survival via NF-κB-dependent induction of EGR1 transcription in PCa cells; Libertini et al (18) described E2F1-dependent modifications of androgen dependence, differentiation, and sensitivity to apoptotic stimuli in PCa cell lines.…”
Section: Introductionmentioning
confidence: 99%